2012
DOI: 10.1080/11250003.2011.621072
|View full text |Cite
|
Sign up to set email alerts
|

Stranded cetaceans as indicators of mercury pollution in the Mediterranean Sea

Abstract: Concentrations of Hg were determined in tissues (muscle, heart, kidney, lung and liver) of two cetacean species (Stenella coeruleoalba and Tursiops truncatus) stranded along the Italian coasts during the period 2000-2009 and compared with those previously reported by other authors from different areas of the Mediterranean basin. The highest concentrations of Hg were found in liver samples of both species (8.4-1752 mg·kg −1 dry weight for S. coeruleoalba and 9.6-1404 mg·kg −1 d.w. for T. truncatus). Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 30 publications
(44 reference statements)
3
12
0
Order By: Relevance
“…1A). In accordance with previous authors (Bellante et al, 2012), an increasing trend throughout the life of cetaceans was observed (Fig. 1), probably due to bioaccumulation from the continuous uptake of Hg in the diet and the decreasing ability to excrete this metal and storage in stable forms such as HgSe (Aguilar et al, 1999;Mackey et al, 1995;Wagemann et al, 2000).…”
Section: Influence Of Sex and Age On Mercury And Selenium Levelssupporting
confidence: 91%
“…1A). In accordance with previous authors (Bellante et al, 2012), an increasing trend throughout the life of cetaceans was observed (Fig. 1), probably due to bioaccumulation from the continuous uptake of Hg in the diet and the decreasing ability to excrete this metal and storage in stable forms such as HgSe (Aguilar et al, 1999;Mackey et al, 1995;Wagemann et al, 2000).…”
Section: Influence Of Sex and Age On Mercury And Selenium Levelssupporting
confidence: 91%
“…IRL bottlenose dolphins have a long life span, bioaccumulate contaminants and display defined home ranges with a high degree of site fidelity (Mazzoil et al, 2008;Bossart, 2011). Apex predators such as dolphins can serve as indicators of THg contamination (Bellante et al, 2011). As a result of biomagnification through the food chain, tissue concentrations reach the highest levels in species at the top of the food web (Kidd et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the toxic effects of some heavy metals, their accumulation through the food web requires constant monitoring in order to apply appropriate and successful mitigation approaches (Bellante et al 2011). Heavy metals from agricultural activities are often discharged into rivers and lakes, and assessing their concentrations has recently become an important component of water pollution monitoring (Canivet et al 2001;Ansaldo et al 2009).…”
Section: Introductionmentioning
confidence: 99%